Obtenção e aplicação biológica de quitinases recombinantes da formiga cortadeira Atta sexdens - Corrêa, Katia Celina Santos (2023)
Chitinases catalyze the cleavage of the β-1,4 bond of chitin, a polysaccharide produced by several organisms including insects. From a biotechnological point of view, these enzymes have potential application in the medical field and in biological control. Despite their importance, insect chitinases have been little studied. The objective of this work was to obtain and characterize three recombinant chitinases from the leaf-cutter ant Atta sexdens, containing different catalytic domains (C) and chitin-binding sites, CBM (B). A. sexdens does not have a known genome, as yet, but from the genome of Acromyrmex echinatior, also a leafcutter, primers were designed and it was possible to amplify DNA from A. sexdens cDNA that were cloned into the pPICZαA vector, to proteins being expressed in Pichia pastoris. The enzymes, called AsChtII-C2B3, AsChtII-C3C4 and AsChtII-C5B1, presented an optimum pH between 4-5 and greater activities at 50 0C using a colloidal chitin as a substrate. Specific activities evaluated showed that the presence of CBM does not interfere with the activity, the AsChtII-C3C4, which does not contain a chitin binding site, having the highest activity in colloidal chitin. The three enzymes were evaluated for fungicidal activity using Candida albicans and Aspergilius fumigatus, human fungal pathogens, as models. The enzyme AsChtII-C5B1 inhibited the growth of C.albicans by 87.6% (at 150 ug/mL) and AsChtII-C2B3 and AsChtII-C3C4 inhibited it by 61% and 54.5%, respectively, at 50 ug/mL. AsChtII-C2B3 and AsChtII-C5B1 inhibited the growth of A. fumigatus by 66% and 61% at 50 ug/mL. The enzyme AsChtII-C3C4, which does not present CBM, inhibited the growth of the fungus by 60% at 25 μg/mL. Another objective of the work was to characterize a previously obtained recombinant chitinase, AsChtII-C4B1, against α-chitin and β-chitin, using a combination of techniques such as 13C NMR, X-ray diffraction, viscosity analysis and SEM-FEG. α- chitin is a constituent of the cell wall of fungi and the exoskeleton of crustaceans and β-chitin is found in squid gladia. The results obtained showed that AsChtII-C4B1 is capable of hydrolyzing α- and β-chitin, showing the biotechnological potential of the enzyme, with its use as a fungicide, insecticide and in obtaining chitosan from crab and shrimp shells being seen, for example. Thus, the interference of AsChtII-C4B1 in the growth of the phytopathogenic fungus Lasiodiplodia theobromae was evaluated. The delay in the development of mycelia with visual changes in the hyphae led to analysis by scanning electron microscopy, SEM, of the same, which showed that treatment with AsChtII -C4B1 caused important changes such as wrinkling, rounding of the edges and holes on the surface of the hyphae. Together, the set of data obtained from the different approaches of the present study showed that the recombinant proteins obtained act on different types of chitin and have great biotechnological potential.